2014
DOI: 10.2337/diaclin.32.3.100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ward Management of Diabetic Ketoacidosis

Abstract: IN BRIEF Ward management of diabetic ketoacidosis (DKA) using subcutaneous insulin in specific patient populations is safe and effective, but insulin administered by continuous infusion has not been analyzed in this setting. This retrospective cohort study utilizing a nursing-driven, continuous infusion insulin calculator demonstrated safe and effective treatment of patients with DKA on medicine wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Currently, we average about 200 IV insulin drips monthly at our institution, including the operating room, recovery room, medical-surgical floors and in the ICUs. 10 Most institutions permit IV insulin drips only in the ICUs as was the practice at our institution until resources were provided to improve hospital diabetes management. Education and support for nursing staff provided an avenue for noncritical adult patients who required an IV insulin drip to be managed on the general medical-surgical units, as well as all the ICUs.…”
Section: Musc Identified the Paper Column-based IV Insulinmentioning
confidence: 99%
“…Currently, we average about 200 IV insulin drips monthly at our institution, including the operating room, recovery room, medical-surgical floors and in the ICUs. 10 Most institutions permit IV insulin drips only in the ICUs as was the practice at our institution until resources were provided to improve hospital diabetes management. Education and support for nursing staff provided an avenue for noncritical adult patients who required an IV insulin drip to be managed on the general medical-surgical units, as well as all the ICUs.…”
Section: Musc Identified the Paper Column-based IV Insulinmentioning
confidence: 99%
“…In the United States of America, 43 % of the total medical costs for diabetes is spent on hospital inpatient care [ 6 ]. The costs of DKA treatment are significant, with estimated mean expenses for a single hospitalization ranging from $7470 to $20,864 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our time to anion gap closure of 10.9-11.5hours was similar to the previously mentioned study that saw 10.3-10.4hours. 22 There were multiple limitations to this study. First, the study was single-centered and utilized a small sample size of thirty patients.…”
Section: Discussionmentioning
confidence: 96%
“…19 However, none of the available data has analyzed factors leading to AGRO in patients with diabetic ketoacidosis. One study evaluated the impact of initiating subcutaneous insulin glargine within twelvehours of intravenous insulin infusion and found that this is a safe method for preventing future hyperglycemia without increased risk of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation